Efeito do tratamento de sementes na redução da incidência e severidade da ferrugem asiática da soja, associado à pulverização foliar e a duas cultivares - Pimenta, Cláudia Barbosa (2009)
Seed treatment with systemic fungicides has the advantage of promoting efficient protection in the initial development of the culture. It has been used for several years, for the control of biotrophic fungi in cereals. It is known that some leaf diseases can be managed through seed treatment with systemic fungicides. Soybean Asian rust is a major disease that attacks soybean crop. Alternative strategies of management have been studied to minimize the damage caused by this disease. The field trail evaluated the effect of seed treatment associated with foliar spray in two soybean cultivars, to reduce the incidence and severity of soybean Asian rust. The field trail was done at the experimental station of SEAGRO, county of Senador Canedo, GO. The design of the field trail was a randomized factorial (3x2x2) with 4 replicates. Two triazole fungicides were evaluated for seed treatment (fluquinconazol and flutriafol), in two soybean cultivars (BRS Valiosa RR and Emgopa 315 RR), complemented with fungicide foliar spraying (azoxystrobin + cyproconazole and nimbus). The following parameters were evaluated: seedling emergence, incidence and severity of soybean Asian rust, defoliation, 1000 seed weight and yield. Severity was evaluated using the diagrammatic scale developed by Canteri and Godoy (2003). Analysis of variance was done for all parameters evaluated, and means were compared by the Tukey test at 5% probability. Seed treatment with fluquinconazol and flutriafol did not affect final stand. At 65 days after sowing, it was observed that Emgopa 315 RR cultivar had lower incidence of soybean Asian rust. Fluquinconazol and flutriafol promoted lower incidence and severity of soybean rust. Emgopa 315 RR had less defoliation than BRS Valiosa RR. Seed treatment with fluquinconazol and flutriafol promoted less defoliation than untreated seeds in BRS Valiosa RR cultivar. Seed treatment with fluquinconazol provided less defoliation. Seed treatment did not affect 1000 grains weight. Seed treatment can be used as a tool for the management of soybean Asian rust.